Study The Relationship Between Helicobacter Pylori Infection And The Level Of Serum Ferritin Using Immunofluorescence Assay Method - Alhamadani, Yousif (Journal of Biomedicine and Biochemistry, 2024)
The Aim of the study was determine the relationship between the pres- ence of Helicobacter pylori infection and the level of S. ferritin using Im- munofluorescence assay method. Methods The study was conducted between (November) 2023 and (February) 2024, where the study was conducted on (100) patients both males 58% and females 42% in the city of Samawah, Iraq, suffering from symptoms of H. pylori. Results showed that 81 patients were confirmed to be infected with H. pylori 54.32% male and 45.67% female. The study also showed that 74.07% of the patients with H. pylori infection suffered from a ferritin deficiency anemia the levels of S. ferritin was between 2.77 - 18.85 ng/ml for male and 0.5 - 12.79 ng/ml for female, and 25.92% of patients they have H. pylori infection but with normal levels of S. ferritin 34.11 - 218.73 ng/ml for male and 22.61 – 81.57 ng/ml for female. This decrease in S. ferritin levels is due Upper Gastrointestinal Bleeding which is due to necrosis and ulceration of the wall lining the upper part of the digestive system by H.pylori. Other 19 patients had no bacterial infection identified in their serum their levels of S. Ferritin was 30.63 – 310.25 ng/ml for male and 15.01 – 124.14 ng/ml for female therefore, this levels within the normal rang.